A 0.05 V driven ammonia gas sensor based on an organic diode with a top porous layered electrode and an air-stable sensing film. Issue 21 (14th May 2019) - Madhaiyan, Govindasamy; Chen, Chao-Hsuan; Wu, Yi-Chu; Horng, Sheng-Fu; Zan, Hsiao-Wen; Meng, Hsin-Fei; Lin, Hong-Cheu
Abstract : In this work, we successfully demonstrated an extremely-low-voltage (0.05 V) gas sensor based on a vertical organic diode with work-function-matched electrodes. Abstract : In this work, we successfully demonstrated an extremely-low-voltage (0.05 V) gas sensor based on a vertical organic diode with work-function-matched electrodes. With the designed electrodes (MoO3 /Al vs. Al), the built-in field in the vertical diode is greatly reduced and hence the diode can be turned on at a very low voltage. By producing nanometer pores in the top electrode, the diode becomes a very sensitive gas sensor to detect ammonia in parts-per-billion (ppb) concentrations. Upon reducing the voltage from 5 V to 0.05 V, this sensor device shows an over 5-times enhancement in the sensitivity. The air-stable sensing film also exhibits a lifetime of 30 days in air. Finally, by connecting with an organic photovoltaic (OPV) device, the gas sensor can be directly powered and switched on by irradiating light on the OPV.